The effect of two inert diets on purple sea urchin, Paracentrotus lividus (Lamarck, 1816) growth and gonadal development, in aquaculture - Loureiro, Paulo Filipe Machado (2021)
The purple sea urchin, Paracentrotus lividus, like other species of sea urchin, is of great economic interest, as its gonads are considered a delicacy. In certain countries, such as Japan, the sea urchin gonads, also known as “uni”, are fully part of the local culture and gastronomy. To respond to the increase in demand, the last decades have been marked by an increase in the capture of wild sea urchins, but, as demand continued to increase and the capture of wild sea urchins was no longer ecologically sustainable, interest in echinoculture emerged. Various studies have shown positive results on somatic and gonadal growth when feed availability is high, nonetheless, the main obstacles encountered in the production of sea urchins are related to feed: difficulty in finding the balance between cost and quality of feed, limited growth due to inadequate diets and poorly optimized and efficient feeding regimes. Thus, it is essential to provide a high-quality feed since the main goal is to maximize production and obtain a final product of high commercial value. The aim of the present study was to determine the effects of two inert diets on somatic and gonadal growth of P. lividus, and to investigate the effects of sea urchin density on their feeding regime and somatic growth. For that, three trials were carried out, a 20-weeks nutritional trial under farm-conditions, with 450 sea urchins, and a 10-weeks nutritional trial under laboratory-conditions, with 180 sea urchins to determine the effect of two inert diets, containing 20% Ulva spp., on somatic and gonadal growth of juveniles P. lividus, and a 10-weeks density trial under lab-conditions, with 360 sea urchins, to investigate the effects of rearing density on growth and nutritional performances. At the end of the trials, P. lividus juveniles fed with inert diets showed higher total wet weight gain (TWWG), higher total specific growth rate (TSGR) and higher gonadosomatic index (GSI) than those fed with fresh Ulva spp. Sea urchins fed with inert diets showed 6 to 7 times lower feed conversion ratios (FCR) and 3 to 4 times higher protein efficiency ratios (PER) than sea urchins fed with fresh Ulva spp. The rearing density (268 ind.m-2) had no impact on growth and nutritional performance of the sea urchins. This study has shown that inert diets containing 20% Ulva spp. are adequate for an echinoculture, under farm or lab-conditions. The diets were able to enhance somatic and gonadal growth, nutritional performance and with none detrimental impact in sea urchins’ health.